Case Report: 1-Year Follow-Up of Vagus Nerve Stimulation in a Dog With Drug-Resistant Epilepsy - Hirashima, Junya; Saito, Miyoko; Igarashi, Hirotaka; Takagi, Satoshi; Hasegawa, Daisuke (Frontiers in Veterinary Science, 2021)
A vagus nerve stimulation (VNS) system was surgically implanted to treat drug-resistant epilepsy in a 5-year-old male Shetland Sheepdog. At regular visits during a one-year follow-up, treatment efficacy and adverse effects were assessed, and programmable stimulation parameters were adjusted to optimize stimulation intensity while avoiding adverse effects. The frequency of generalized tonic-clonic seizures was reduced by 87% after the initiation of VNS. The owner reported that the dog regained his personality and the quality of life of both the dog and owner improved. The only adverse effect of VNS was a cough that was controlled by adjusting stimulation parameters. There were no surgical complications or other issues with the VNS device. This is the first long-term evaluation of VNS therapy in a dog, and the results obtained suggest that gradual adjustments of VNS parameters facilitate optimum VNS dosing.